ANALISIS PERAN DAN KEWENANGAN BADAN PENGAWAS PEMILIHAN UMUM DALAM PENYELESAIAN DUGAAN PELANGGARAN ADMINISTRATIF: Jurnal hukum Tata Negara - Syarifudin, Syarifudin; Wandi, Wandi; Jamri, Jamri (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2024)
The core meaning of general elections (elections) in the context of democratic political life is as an institution for changing power which is carried out with standards, regulations, and ethics. In terms of the process, it cannot be separated from the history of the election itself, which began in 1971 as the second election in the history of elections in Indonesia. At that time, there was a crisis of confidence in election organizers due to allegations of widespread manipulation. Since then, the background to the formation of election monitoring institutions has become increasingly clear. The crisis continued in the 1977 election, where more massive fraud and violations occurred. However, it was only in 1982 that an election supervisory institution was formed with the name of the General Election Oversight Committee (Panwaslak Pemilu) as a refinement of the General Election Institution. The role and authority of Bawaslu in handling election administration violations start from the findings of City Panwaslu members, the formation of an examination panel led by the Chair of Bawaslu, an examination hearing, and finally the holding of a final hearing. decision. There are three obstacles at this stage, namely the difficulty of presenting witnesses at the trial, limited authority to execute decisions, and a lack of institutional members to carry out their duties during the trial. Inti makna dari pemilihan umum (pemilu) dalam konteks kehidupan politik yang demokratis adalah sebagai sebuah lembaga untuk pergantian kekuasaan yang dijalankan dengan standar, peraturan, dan etika. Dalam hal proses, tidak dapat dipisahkan dari sejarah pelaksanaan pemilu itu sendiri, yang dimulai pada tahun 1971 sebagai kali kedua dalam sejarah pemilu di Indonesia. Pada waktu itu, muncul krisis kepercayaan terhadap petugas pemilu akibat dugaan manipulasi yang marak dilakukan. Sejak saat itu, latar belakang terbentuknya lembaga pengawas pemilu menjadi semakin jelas. Krisis terus berlanjut pada pemilu 1977, di mana terjadi kecurangan dan pelanggaran yang lebih masif. Namun, baru pada tahun 1982, lembaga pengawas pemilu dibentuk dengan nama Panitia Pengawas Pelaksanaan Pemilihan Umum (Panwaslak Pemilu) sebagai penyempurnaan dari Lembaga Pemilihan Umum. Peran dan kewenangan Bawaslu dalam menangani pelanggaran administratif pemilu dimulai dengan temuan dari anggota Panitia Pengawas Pemilihan Umum Kecamatan Kota, pembentukan majelis pemeriksa yang dipimpin oleh Ketua Bawaslu, persidangan untuk pemeriksaan, dan akhirnya pembuatan putusan akhir, terdapat tiga hambatan pada tahap ini, kesulitan dalam mendatangkan saksi dalam persidangan, keterbatasan kewenangan dalam eksekusi putusan, dan kekurangan anggota lembaga untuk menjalankan tugas saat persidangan berlangsung.